A Preliminary Study to Evaluate Recovery in Environmental Microplastic Analysis - İrem Öztürk; Dilara Cinci; Fatma Nur Eraslan; Mansoor Ahmad Bhat; Eftade O. Gaga; Kadir Gedik (Doğal Afetler ve Çevre Dergisi)
Microplastics (MPs) have attracted attention as a global concern due to their physicochemical properties, structural components, role as vectors for pollutants and potential health impacts. In studies focusing on the occurrence, levels, and distribution of MPs, there is a need for recovery studies since certified reference materials or standard methods have not yet been established for quality assurance in analyses. In this study, it was aimed to evaluate the recovery efficiency of MP analyses in soil and air matrices using an analyte addition approach. Recovery studies were carried out by soil samples taken from the garden of Eskişehir Technical University campus and dust samples taken from the indoor environment of the building in the size range of 1-5 mm with the addition of polyethylene (PE) type (<1000 µm) microplastics on a number or mass basis. MPs in the samples, which underwent a series of experimental processes, such as density separation (NaCl) and organic removal (30% H2O2), were later visually inspected with a stereo microscope and then identified with an Attenuated Total Reflectance (ATR)-Fourier Transform Infrared (FTIR) spectrometer. Polyethylene, Tencel, and Polyacetylene (>70% matching rate) type MPs were detected in soil and dust samples, mainly in the form of fibers and fragments, with sizes ranging between 57.0-4989 µm and 36.2-2636 µm, with an average of 1.43±0.574 MP/g and 5500±2531 MP/g, respectively. In the recovery studies, an average recovery rate of 75% was achieved in trials where PE was added to the samples by mass and 100% in trials where PE was added by number. The recovery studies, which were also evaluated in terms of the factors affecting MP analysis, were examined in the context of current literature, and recommendations were made.